Updates on geographic range and synonymies in species of Podocoma (Asteraceae: Astereae) - Deble, Leonardo Paz (Balduinia, 2021)
Abstract. The geographic range of Podocoma Blanchetiana includes the sandy grasslands (Campos de Areia region), in Alegrete, Manoel Viana and São Francisco de Assis municipalities, southwest Rio Grande do Sul state, Brazil. Furthermore, Stenachaenium megapotamicum var. pedunculata and St. megapotamicum f. minor, are added to the synonymy of P. hieracifolia. Lectotypes are designated to St. megapotamicum f. minor and Podocoma Blanchetiana var. intermedia.